The concept of a competent person in criminal proceedings (Journal of actual problems of jurisprudence, 2018)
The article explores the concept of competent persons whose assistance is used in criminal proceedings. The author identifies the common and distinctive features of knowledgeable persons as parties to the proceedings,defines the concepts of “knowledge” and “extensive knowledge”.Is determined by the value of the legal institution of professional advice during the preliminary investigation and during the court proceedings.Key words: evidence, proving, justice, competent person, specialist, special knowledge, criminal procedure.